(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Using the GMAS questionnaire to assess medication adherence and certain related factors in outpatients with type 2 diabetes mellitus at An Binh Hospital. Subject and method: A cross-sectional descriptive study was conducted on 255 outpatients with type 2 diabetes mellitus from February 2023 to July 2023. The GMAS medication adherence questionnaire was used to interview the patients. Results: Among outpatients with type 2 diabetes, 76.5% adhered to their medication regimen, while 23.5% did not. There was a significant association between factors such as occupation, disease duration, and the most recent blood glucose levels in the adherence and non-adherence groups (p < 0.05). The medication-adherent group had more stable fasting blood glucose levels compared to the non-adherent group. Additionally, patients with a longer duration of diabetes demonstrated better adherence compared to other groups. Conclusion: Outpatients with type 2 diabetes mellitus at An Binh Hospital demonstrated relatively good medication adherence (76.5%). The study identified several factors influencing adherence behavior. Occupation, duration of illness, and blood glucose levels positively affect medication adherence behavior. From these findings, we have developed the most appropriate health education strategies to increase patient adherence and prevent dangerous complications associated with type 2 diabetes mellitus